Production of Third-Person Singular –s And be Copula in Communication Tasks by Vietnamese EFL Learners: Acquisition Order and Learner Orientation to Form - Nguyen, Bao Trang Thi; Newton, Jonathan (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
Research on the acquisition order of inflectional morphemes in English has shown that third-person singular –s (3SG–s) is challenging to acquire and acquired later than be copula by both L1 and L2 learners of English. In a departure from the usual practice of controlled elicitation, the current study investigated the production of these two forms by Vietnamese EFL learners in oral communication tasks performed in intact classrooms. Vietnamese L1 does not inflectionally mark 3SG–s although the construction of be copula in Vietnamese and English shares some features. These differences motivated the selection of the two target forms. Nine pairs of Vietnamese EFL university students were recorded performing five communicative tasks generated contexts for use of 3SG–s. over three weeks in their normal classes. Performance data were transcribed and analyzed for frequencies of production and omission of the two target forms in obligatory contexts. After completing the tasks, the students were interviewed about what they attended to when performing the tasks. Interview transcripts were analyzed thematically. Results show that the learners omitted 3SG–s in most obligatory contexts and across all tasks. They were better at accurately producing be copula than 3SG–s but accuracy rates varied between learners. Interview data revealed the conscious decisions learners made concerning the accuracy of their language production. The findings are discussed with reference to different theoretical models. The study advances understanding of acquisition of 3SG–s and be copula by EFL learners and offers pedagogical implications for how a focus on inflectional forms can be managed in oral communicative task performance.